Part I: Development of sample preparation method for analysis of total iodine in air filters. Part II: Application of Inductively coupled plasma-mass spectrometry in analysis of radionuclides-uranium and plutonium - Tiong, Diane Ling Ying (2018)
In Chapter one, an acid assisted closed vessel microwave digestion procedure was developed for the treatment of fine airborne particulate matter that allows elemental iodine to be solubilised simultaneously with metallic elements. This procedure is an improvement over existing methods as it allows the iodine to be safely digested from the filter media (polypropylene or cellulose) in less than one hour and achieve up to 70–100 % recoveries, without requiring an overnight pre-digestion step or the addition of reducing agents, with a microwave temperature of 185 °C and the use of 65 % HNO3 in the digestion media. A range of filters were investigated to determine the material that has the best properties for microwave digestion that also enabled the deposited iodine present in total suspended particles (TSP) to be rapidly fully digested and quantitatively analysed using inductively coupled plasma-mass spectrometry (ICP-MS). This developed method has shown to be possible in the analysis of metallic elements with iodine of interest without the need of a separate chemical preparation steps. The following Chapters 3 and 4 are based on the analysis of radioactive isotopes of uranium and plutonium with the use of a quadrupole ICP-MS with a general introduction on radionuclide analysis in Chapter 2. Unlike other mass-spectrometric methods (eg,, Sector-field ICP-MS or Multi-collector ICP-MS), the quadrupole ICP-MS is a cost-effective (easier maintenance) analytical instrument with good sensitivity to sub-ppb levels In Chapter 3, plutonium analysis, in particular 238Pu, was performed with a non-radiometric method. 238Pu is an alpha emitter and hence can be analysed successfully with alpha spectrometry, which does not have any spectral interference although it is a very slow alpha emitter and requires a relatively long counting time. However, mass spectrometric analysis of 238Pu faces isobaric interference with interfering 238U which cannot be resolved. Therefore, in this chapter, a mass spectrometric method that uses an experimentally derived algebraic correction factor was developed that requires sample pretreatment with TEVA and UTEVA resin cartridges to separate the plutonium (TEVA) and uranium (UTEVA) in the sample. The proposed developed method was shown to be more effective when enriched uranium (weapon grade) was added into the sample prior to the resin-based separation steps. In chapter 4, analysis of uranium isotope samples has usually been performed in a clean-room facility due to the presence of natural uranium in the environment that can potentially contaminate the sample. However, a clean room facility is not available in many laboratories that also carry out ICP analysis. There is also a lack in understanding of the potential contributors to natural uranium contamination, which can be identified through analysis of the process blanks. In this study, the process blanks were analysed in parallel to all samples to enable blank corrections to be performed for every step of the sample treatment processes. A significant portion of the natural uranium contamination was found to derive from reagents and consumables. The capability of analysis of different enrichment levels of uranium samples were evaluated by varying the amount of samples spiked during the sample preparation technique (lithium borate fusion) and assessed with the related relative uncertainties at the various mass point of spiked samples. The thesis ends with a concluding Chapter 5.